Philippians and Philemon - Thurston, Bonnie Bowman; Ryan, Judith, 1952-; Harrington, Daniel J. (Collegeville, Minn. : Liturgical Press, 2005)
"Translations with commentary of Paul's Letter to the Philippians and his Letter to Philemon. The letters are approached methodologically, with attention to historical and cultural contexts"--Provided by publisher.
"A Michael Glazier book."
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries; Bible. -- Commentaries